Analysis of the factors of intention to use QRIS for MSMEs in Semarang City’s traditional market - Risma Nurhapsari; Erlinda Sholihah (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
Quick Response Indonesian Standard (QRIS) is the standardization of QR codes as a technology for payment systems established by Bank Indonesia on January 1, 2020. This standardization was formed to provide an easier and more efficient cashless payment system, especially for MSMEs. This study targets to analyze factors, namely product knowledge, perceived usefulness, perceived ease of use, and perceived risk of the intention of using QRIS in Traditional Market MSMEs in Semarang City. The model in this study was developed from the Technology Acceptance Model (TAM) framework and adapted to the context of MSMEs in Indonesia. This research uses an associative quantitative approach. The population in this study was traders in seven traditional markets in the Semarang City area. As empirical data was collected through a questionnaire involving 105 respondents from traders in the traditional market of Semarang City, then analyzed with SEM-PLS analysis techniques with SmartPLS software. The results showed that product knowledge, perceived usefulness, and perceived ease of use positively and significantly affected the intention of using QRIS. Then, perceived risk negatively and significantly affects the intention of using QRIS